A new route to porous metal–organic framework crystal–glass composites. Issue 36 (4th September 2020) - Li, Shichun; Yu, Shuwen; Collins, Sean M.; Johnstone, Duncan N.; Ashling, Christopher W.; Sapnik, Adam F.; Chater, Philip A.; Keeble, Dean S.; McHugh, Lauren N.; Midgley, Paul A.; Keen, David. A.; Bennett, Thomas D.
Abstract : A lower temperature route to metal–organic framework crystal–glass composites is presented. Specifically, the annealing pre-formed ZIF-62 glass with a crystalline MOF above T g will enable formation of a greatly expanded range of materials. Abstract : Metal–organic framework crystal–glass composite (MOF CGC) materials consist of a crystalline MOF embedded within a MOF–glass matrix. In this work, a new synthetic route to these materials is demonstrated through the preparation of two ZIF-62 glass-based CGCs, one with crystalline ZIF-67 and the other with crystalline UiO-66. Previous attempts to form these CGCs failed due to the high processing temperatures involved in heating above the melting point of ZIF-62. Annealing of the ZIF-62 glass above the glass transition with each MOF however leads to stable CGC formation at lower temperatures. The reduction in processing temperatures will enable the formation of a greatly expanded range of MOF CGCs.